A Comparative Study: Anxiety as an Impact of Slavery in Toni Morrison’s Beloved and William Faulkner’s Absalom, Absalom! - Bhakti Satrio Nugroho (J-Lalite: Journal of English Studies, 2021)
This paper discusses the anxiety as an impact of slavery reflected in two outstanding African-American novels: Toni Morrison’s Beloved and William Faulkner’s Absalom, Absalom!. These novels are set in around the slavery period which shows how cruel and brutal slavery practices in the United States. The plots consist of some traditions and beliefs among White and African-American which have emerged since the antebellum period. By using a comparative approach, this paper focuses on the types of anxiety mentioned by Sigmund Freud. The analysis shows that both neurotic and moral anxieties play a pivotal psychological element throughout the intense “black-white” binary narratives. In this case, Toni Morrison’s Beloved consists of neurotic anxiety in the form of trauma experienced by Sethe and William Faulkner’s Absalom, Absalom! consist of moral anxiety in the form of shame for having Negro bloodline in aristocrat Southern plantation culture. Both novels show that slavery, whether it stands as a tradition or as an economic value, has significantly shaped the direction of American society.